EDUKASI TAHAPAN TUMBUH KEMBANG ANAK SEBAGAI UPAYA PENCEGAHAN KETERLAMBATAN PERKEMBANGAN ANAK PADA MASA PANDEMI COVID-19 - Cicilia Febriani Hayuningrum; Nesi Nesi; Dela Fariha Fuadi; Andrew Wijaya Saputra; Putri Karina Syahfitri (LPPM Universitas Pekalongan, 2022)
Corona Disease-2019 (COVID-19) has been widely spread around the world, including Indonesia. There are 977,000 cases and 27,664 from 34 provinces in Indonesia caused by COVID-19 pandemic. Government’s regulations to control COVID-19 are having a widespread impact in every aspect of live, including children’s lives. Physical distancing is one of the most important regulation that applied by almost all countries to control the COVID-19 spread. This regulation also affects the developmental of children, physically and psychologically. Healthcare worker has a duty to prevent the delayed of children’s development during COVID-19 pandemic by doing promotion to the parents about the child developmental stages. With the purpose that this promotion could improve parent’s knowledge about developmental stages of their children. Moreover, they could do stimulation to keep their children’s development optimal during this pandemic condition. The methods used in this activity are seminar and discussion section between the professionals and participants.